BIOM-19. NEXT-GENERATION SEQUENCING (NGS) FOR IDENTIFYING ACTIONABLE MOLECULAR ALTERATIONS IN NEWLY DIAGNOSED AND RECURRENT IDHWT-GLIOBLASTOMA (GBM) PATIENTS: A LARGE MONO INSTITUTIONAL EXPERIENCE. (14th November 2022) - Padovan, Marta; Maccari, Marta; Bosio, Alberto; Vizzaccaro, Salvatore; Cestonaro, Ilaria; Corrà, Martina; Caccese, Mario; Cerretti, Giulia; Fassan, Matteo; Zagonel, Vittorina; Lombardi, Giuseppe
Abstract: BACKGROUNDNGS: panels allow the identification of alterations within hundreds of cancer-related genes and can guide a personalized strategy in glioma treatment. METHODS: From Nov 2019 to Jan 2022 at Veneto Institute of Oncology, Padua, Italy, a large cohort of IDHwt-GBM tissues was analyzed by NGS (FoundationOne®CDx). We identified all potential actionable molecular alterations at diagnosis and/or at recurrence. High tumor mutational burden (TMB) was defined as ≥10 mutations/megabase. RESULTS: We analyzed 429 IDHwt-GBM samples: NGS profile was available for 419 samples (97.7%); sample failures in 10 cases (2.3%). 351 (84%) and 68 (16%) GBM samples derived from surgery at diagnosis and recurrence, respectively. All patients received radiotherapy and/or temozolomide as first line therapy. Among all the analyzed samples, the most frequent actionable molecular alterations were: CDKN2A (57%), CDKN2B (53%), EGFR amplification (39%), EGFR mutation (24%), PTEN loss (27%), RB1 (23%), NF1 (18%), PIK3CA (18%), CDK4 (15%), MDM2 (10%), PDGFRA (8%), BRCA1-2 (7%), FGFR1-3 (7%), Myc (6%), JAK (6%), ROS1 (5%), METmut (2%), METampl (2%), BRAF V600E (2%). No NTRK1/2/3 druggable alterations were observed. High TMB was found in 18 samples. The incidence of alteration of EGFR (ampl/mut), RB1, PIK3CA was statistically different between the two subgroups of newly diagnosed and recurrent GBM samples (Fisher test). To date, 10% of patients received a personalized treatment as compassionate use, off-label use or in clinical trials (9 Dabrafenib/Trametinib, 8 Alpelisib, 3 Erdafitinib, 2 Ipatasertib, 1 Alectinib, 1 Capmatinib, 1 Palbociclib, 1 Entrectinib, 1 Pamiparib). Activity analysis is still ongoing. CONCLUSIONNGS: is feasible in GBM samples. Potentially, a high rate of patients could receive a personalized treatment. The activity analysis is ongoing. However, the incidence of actionable molecular alterations may differ between diagnosis and recurrent GBM samples.